Pengembangan Lembar Kerja Peserta Didik Berbasis Praktikum Model Problem Based Pada Pembelajaran IPS - Armawati Hidayati; Mustaji Mustaji; Hari Sugiharto (The Indonesian Journal of Social Studies, 2019)
This study aims to: (1) Test the feasibility of student worksheets based on the practice of Problem based learning models in social studies (2) Test the effectiveness of student worksheets based on Problem based learning models for changes in student learning outcomes in social studies. The research on the development of this learning media is based on the ADDIE model. The research subjects were seventh grade students of SMPIT Insan Permata Bojonegoro. The selection of subjects by random or random sampling was class VII A as a treatment class with 30 children and class VII B as a control class with 30 children. The results of this study indicate. First, teaching materials in the form of worksheets for social studies -based practicum students in PBL models according to learning experts fall into the criteria of "feasible". According to the material expert on the contents of the material on the social studies student worksheets Integrated practicum based on the results of validation stated "very feasible". And the validation results from media experts get the category "feasible". In general, student worksheets fall into the "very feasible" category. The effectiveness test shows that there are significant differences between classes using LKPD and classes that do not use. This is indicated by the average posttest values between the experimental class and the control class which also differ significantly.